PENGARUH KEPEMIMPINAN, KOMUNIKASI, KOMPENSASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI - Sutrisno, Mulyanto & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2007)
ABSTRACT Human resource development is not only to increase the quality of human resource in Indonesia but also to increase the quality of government employees which have the trait and behavior based on loyalty, honesty, discipline, and has high motivation, so it give best services to society. This research takes the sample of 30 respondents of the employees in Dinas Pendapatan Daerah Kota Surakarta. The analysis using in this research are multiple regression analysis with t test, F test, and coefficient determination test to the hypothesis. The summaries of this research are as follows: leadership does not influence individually to employee performance. Communication influence individually to employee performance. Motivation does not influence individually to employee performance. The suggestion given to this research are as follows: it is needed the higher attention to compensation to all employees in Dinas Pendapatan Daerah Kota Surakarta in order to increase the employee performant it is done with giving the compensation to all employee wisely and correctly because compensation gives the influence to employee performance significantly. It is needed the higher attention to compensation to all employees in Dinas Pendapatan Daerah Kota Surakarta in order to increase the employee performant. It is done with increase the relationship between leader and employee, employee and employee, and employee with follower. Keywords:       leadership, communication, compensation, motivation, employee performance